Предмет: Математика,
автор: kerimovkyamal
помогите решить -5(х+3)+4(х-2)-6(2х+1)
Ответы
Автор ответа:
1
-5(х+3)+4(х-2)-6(2х+1)= -5х-15+4х-8-12х-6=-13х-29
Ответ. -13х-19
Автор ответа:
1
-5(х+3)+4(х-2)-6(2х+1) = -5x-15+4x-8-12x-6=
=-13x -29
(PS: Если это уравнение , то еще: -13x -29=0; 13x=-29; x=-29/13)
=-13x -29
(PS: Если это уравнение , то еще: -13x -29=0; 13x=-29; x=-29/13)
Похожие вопросы
Предмет: Русский язык,
автор: mikhailsmirnov2
Предмет: Русский язык,
автор: Яна775975
Предмет: Русский язык,
автор: УМНИК23451
Предмет: Английский язык,
автор: CleverLate
Предмет: Геометрия,
автор: Кирилл0577